Additive Neuroprotective Effect of Borneol with Mesenchymal Stem Cells on Ischemic Stroke in Mice - Zhang, Xiao-Guang; Shan, Chang; Zhu, Jia-Zhen; Bao, Xiao-Yi; Tong, Qiang; Wu, Xi-Fan; Tang, Xiao-Chen; Xue, Ting; Liu, Jie; Zheng, Guo-Qing; Wang, Yan (Frontiers in Physiology, 2018)
Intravenous stem cell transplantationt initiates neuroprotection related to the secretion of trophic factor. Borneol, a potential herbal neuroprotective agent, is a penetration enhancer. Here, we aimed to investigate whether they have additive neuroprotective effect on cerebral ischemia. Borneol was given to mice by gavage 3 days before middle cerebral artery occlusion (MCAO) induction until the day when the mice were sacrificed. Mesenchymal stem cells (MSCs) were intravenously injected at 24h after MCAO induction. Neurological deficits, infarct volume, cell death and neurogenesis were evaluated. Combined use of MSCs and borneol could more effectively reduce infarction volume and cell apoptosis, enhance neurogenesis, and improve the functional recovery than that of MSCs alone. The findings showed that combined use of borneol and stem cells provided additive neuroprotective effect on cerebral ischemia. However, the supposed effect of borneol on the improved MSC penetration still needs further direct evidence.